Polyunsaturated and Very‐Long‐Chain Fatty Acids Are Involved in the Adaptation of Maloideae (Rosaceae) to Combined Stress in the Mountains. Issue 1 (9th January 2020) - Voronkov, Alexander S.; Ivanova, Tatiana V.; Kumachova, Tamara K.; Kozhevnikova, Anna D.; Tsydendambaev, Vladimir D.
Abstract: One of the mechanisms of plant adaptation to combined stress under conditions of altitudinal zonation is changing the lipid fatty acid (FA) composition. The main changes in the FA composition occurred in the outer cell layers of the pericarp, but not in the parenchyma. Adaptation was found to be species‐specific. In Cydonia oblonga Mill . and Malus domestica Borkh ., the ratio of polyunsaturated 18:2 and 18:3 lipid FAs changed with increasing height, while a constitutive level of the unsaturation index (UI) and low contents of very‐long‐chain fatty acids (VLCFAs) were maintained. Mespilus germanica L. was characterized by a higher level of VLCFAs due to the high content of 20:0. The sum of VLCFAs in medlar increased by up to 16 % with changing altitude, which was accompanied by the changes in the ultrastructure of chloroplasts and a noticeable decrease in the UI. We attribute the differences in the adaptive strategies in C. oblonga, M. domestica and M. germanica to specific structural features of the pericarp peel. Despite different adaptation mechanisms, the studied species can grow equally successfully at the altitudes from 300 to 1200 m. Abstract :